CLAY VESSELS’ SHAPES AS AN OBJECT OF STUDY OF THE CULTURAL HISTORY OF ALANS OF THE FOREST-STEPPE DON REGION - Suhanov, Evgenij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2022)
Alans are one of the ethnic components of the Saltovo-Mayatsk archaeological culture. Antiquities associated with this group are found in the Middle Don basin. The article studies the cultural characteristics of the Alanian groups that left behind the burial sites of this region, on the example of pottery. The object of study are the shapes of clay vessels. The study was carried out according to the methodology developed within the framework of the historical-and-cultural approach to the study of ancient pottery, proposed by A.A. Bobrinsky. The article considers the quantitative composition of unmixed traditions of shaping forms of pottery on sites associated with the Alan component of the Saltovo-Mayatsk culture. The three most numerous categories of ware are analyzed: jugs, mugs and pots. The communities that left behind the catacomb burial grounds of the eastern regions of the Don forest-steppe were culturally more heterogeneous than the communities from the western part. The materials of the Mayatsky complex, Yutanovsky and Podgorovsky burial grounds present unique and inherently mixed sets of morphological traditions. Based on the data of the study of ceramics and their comparison with burial traditions, we consider the Yutanovsky, Podgorovsky, Mayatsky burial grounds as cemeteries of communities that included settlers from the western part of the Don forest-steppe, whose traditions mixed up in new places of residence. The most probable reason for the resettlement of a certain part of the Alanian population to the eastern regions of the forest-steppe Don region can be considered the construction of a series of stone and brick fortresses on the Tikhaya Sosna River, as well as the need to control this section of the Slavic-Khazar frontier. In accordance with the concept, proposed by G.E. Afansiyev, these fortifications were built in the 30-40s of the 9th century. The author suggests that it is these events that can explain the influx of the Alanian population into the eastern regions of the forest-steppe Don region and the formation of more culturally heterogeneous groups in the new places of residence of these people than among the “neighbors” from the western regions of the Don forest-steppe.
Keywords: Alans; Saltovo-Mayatsk culture; pottery; vessel shapes